Mangrove restoration and coastal flood adaptation: A global perspective on the potential for hybrid coastal defenses - Timothy Tiggeloven; Vincent van Zelst; Eric Mortensen; Bregje K. van Wesenbeeck; Thomas A. Worthington; Mark Spalding; Hans de Moel; Philip J. Ward (Proceedings of the National Academy of Sciences, 2026)
To reduce current and future coastal flood risk, it is critical to better understand how adaptation measures, including nature-based solutions, can reduce that risk. Globally, hybrid coastal defenses, including a combination of coastal vegetation, such as salt marshes and mangroves, with a dike or sea wall, have been highlighted as a promising adaptation measure. Here, we present a global-scale assessment of the potential risk reduction from mangrove restoration in combination with foreshore dike systems under scenarios of climate and socioeconomic change. We provide a quantitative assessment of the benefits in terms of reduced economic damage, exposed population, and poverty exposure. We evaluate mangrove restoration fronting dikes by accounting for wave–vegetation interaction. If mangrove foreshore dike systems were established along coastlines susceptible to flooding, restoration could potentially reduce expected annual damage by US$800 million and reduce expected affected population by 140,000 annually. These values increase under future projections. Our benefit–cost analysis finds mangrove restoration economically viable for about half of the subnational regions assessed (85 to 105 out of 208). At the global scale, the benefit–cost ratio under future conditions ranges from 3 to 6, with a net present value between US$44 billion and US$125 billion. Because absolute risk values and benefit–cost analysis do not differentiate between relative wealth impacts, we also estimated restoration impacts across different wealth levels. We show that restoring mangroves disproportionately benefits people with lower incomes, as they are often more exposed to coastal flooding and located in areas suitable for mangrove restoration. As such, mangrove restoration in low- and middle-income countries could contribute to the resilience of people in poverty.